2004
DOI: 10.1207/s15327027hc1601_4
|View full text |Cite
|
Sign up to set email alerts
|

Religious Identity and Smoking Behavior Among Adolescents: Evidence From Entering Students at the American University of Beirut

Abstract: This survey investigation examines the association between religious identity and smoking behavior in a sample of older adolescents entering the university in Beirut, Lebanon. A culturally appropriate item of religiosity was developed for data collection. Results suggest that religious identity is inversely associated with regular smoking among male and female adolescents, after adjusting for sociodemographic, behavioral, personal, and environmental risk factors. The pattern of associations between weak religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, the relationship between substance misuse and religiosity/spirituality among adolescents is not clear. Accordingly, studies have found that the influence of different religions on the consumption of substances is variable [10][11][12]. Parental factors and parental (i.e., familial) monitoring have generally been found to be protective against cigarette smoking, and studies have been consistent in this regard irrespective of differences in the study populations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between substance misuse and religiosity/spirituality among adolescents is not clear. Accordingly, studies have found that the influence of different religions on the consumption of substances is variable [10][11][12]. Parental factors and parental (i.e., familial) monitoring have generally been found to be protective against cigarette smoking, and studies have been consistent in this regard irrespective of differences in the study populations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand there are some protective factors even though data are not so robust. Parents or friends who do not smoke [23,24], negative beliefs about smoking [24], sports participation [25] and religious identity [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Scholars have previously shown how religious affiliation has influenced health behavior in the general population by reducing risk behaviors such as smoking (Soweid, Khawaja, & Salem 2004; Sinha, Cnaan, & Gilles 2007; Ysseldyk, Matheson, and Anisman 2010). Ysseldyk, Matheson, and Anisman (2010), for example, noted that individuals who highly identify with religious groups utilize this affiliation as a central aspect in developing self-concept, bonding to others with the same affiliation, and gaining self-esteem.…”
mentioning
confidence: 99%